2009
DOI: 10.1021/nl802907d
|View full text |Cite
|
Sign up to set email alerts
|

Charge Carrier Separation in Modulation Doped Coaxial Semiconductor Nanowires

Abstract: Complementary doped donor and acceptor dipoles effectively generate confinement potentials for carriers across a p-type/intrinsic/n-type coaxial nanowire due to the lineup of charge neutrality level. In order to verify this physical picture, we employ first-principles density functional theory to study the confinement of electrons and holes in complementary boron (p-type) and phosphorus (n-type) doped coaxial silicon nanowires. An analysis of the charge density distributions reveals that the electrons and hole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 18 publications
1
37
0
Order By: Relevance
“…Recent experimental and theoretical work on core-shell and core-multishell nanowire heterojunctions provides the capability of forming type II heterojunctions for use in solar cells. [10][11][12][13][14] Since it has been found that multiple excitons per photon can be generated in nanocrystals, designing new photovoltaic cells based on a novel charge separation scheme is needed at nanoscales. It is now possible to separate electrons and holes within a pure nanocrystal by morphology control or partial strain, instead of conventional doping or blending with other materials.…”
Section: Introductionmentioning
confidence: 99%
“…Recent experimental and theoretical work on core-shell and core-multishell nanowire heterojunctions provides the capability of forming type II heterojunctions for use in solar cells. [10][11][12][13][14] Since it has been found that multiple excitons per photon can be generated in nanocrystals, designing new photovoltaic cells based on a novel charge separation scheme is needed at nanoscales. It is now possible to separate electrons and holes within a pure nanocrystal by morphology control or partial strain, instead of conventional doping or blending with other materials.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Among these nanostructures-embedded solar cells, the ones which apply radial p-n junction Si nanostructures are most attractive because they take advantage of all the effects above. 8,9 In 2007, Lieber Charles established Si nanopillarbased radial p-n junction solar cell, grown via vapor-liquidsolid (VLS) method. 10 In 2010, Garnett and Yang fabricated ordered Si nanowire radial p-n junction array solar cells with efficiency over 5% via deep reactive-ion etching (DRIE).…”
mentioning
confidence: 99%
“…The overgrowth of different materials on the exposed facets leads to a prismatic heterostructure that confines eventually the free carriers either at the heterointerface or in the lower-gap semiconductor layer. 26 The two FIG. 11.…”
Section: Discussionmentioning
confidence: 99%